Application of Islamic Education and Moral Education Based on the Merdeka Curriculum in Senior High Schools - Nimas Putri Wulan; Junaidi Sahlan (Jurnal Indonesia Kajian Pendidikan Islam, 2026)
Background: The implementation of the Merdeka Curriculum in Islamic Religious Education and Character Education at the Senior High School level still faces challenges, including limited teacher competence, inadequate learning facilities, and difficulties in implementing holistic assessment, which may affect the strengthening of students’ religious and moral character. Objective: This study aims to analyse the implementation of Islamic Religious Education and Character Education in the Merdeka Curriculum at the Senior High School level, focusing on lesson planning, instructional implementation, and learning evaluation. Method: This study employed a qualitative, descriptive research design. Data were obtained from official documents, scientific journals, reference books, and various relevant academic publications. Data analysis was conducted using content analysis techniques. Result: The findings indicate that the implementation of the Merdeka Curriculum in Islamic Religious Education and Character Education has been effective through differentiated learning, diagnostic assessment, contextual teaching modules, and holistic assessment. However, several challenges remain, including limited teacher competence and inadequate learning facilities. Conclusion: The implementation of the Merdeka Curriculum in Islamic Religious Education and Character Education at the Senior High School level has generally supported more adaptive, student-centred learning practices, although improvements in teacher competence and educational facilities are still required to optimise its implementation. Contribution: This study contributes to strengthening the discourse on the implementation of the Merdeka Curriculum in Islamic Religious Education and Character Education at the Senior High School level.